CD56+ T cells are increased in kidney transplant patients following cytomegalovirus infection. Issue 4 (3rd July 2015) - Almehmadi, M.; Hammad, A.; Heyworth, S.; Moberly, J.; Middleton, D.; Hopkins, M.J.; Hart, I.J.; Christmas, S.E.
Abstract Background CD56+ T cells previously have been identified as potentially cytotoxic lymphocytes, and relative numbers are increased in some infectious diseases. Patients and methods Relative proportions of CD56+ T cells were measured by flow cytometry in groups of renal transplant patients differing in cytomegalovirus (CMV) status of donor (D) and recipient (R). These measurements were related to episodes of CMV viremia. Results Patient groups in which recipients (R+) or donors (D+/R−) were CMV+ had significantly higher proportions of CD56+ T cells (5.11 ± 0.69% and 5.42 ± 1.01%, respectively) than the D−/R− group (1.9 ± 0.35%; P = 0.0018 and 0.017, respectively). In the high‐risk D+/R− group, it was found that patients who had post‐transplant CMV viremia had higher levels than those who remained CMV negative (9.09 ± 2.34% vs. 3.16 ± 1.22%; P = 0.01). CD56+ T cells from R+ and D+/R− groups had higher proportions of both CD4+ and CD8+ cells than the D−/R− group. When activation markers were examined, some CD56+ T cells from both CMV+ groups had a TEM phenotype, with significantly more expressing CD45RO and NKG2C, and less expressing CD28, CD62L, CD127, and CD161 compared to the D−/R− group. Some CD56+ T cells showed specificity for CMV antigens and similar proportions of CD8+ cells were positive for class I HLA‐CMV tetramers containing immunodominant CMV peptides compared to the majority CD56− T cells. Conclusion The results show significant increases in proportions of CD56+ T cells in relation to CMV infection in renal transplant patients and suggest that these cells have a cytotoxic function against CMV‐infected cells.